Ciclo de vida e ecologia de Paspalum fasciculatum Willd. ex. Fluegge (Poaceae), na várzea da Amazônia central - Conserva, Auristela dos Santos; Piedade, Maria Teresa Fernandez (Acta Amazonica, 2001)
Paspalum fasciculatum is a robust perennial C4 grass that occurs in the Central Amazon várzeas. In order to establish the ecology and life cycle of the species in relation to the annual water level fluctuations, twenty plants were randomly selected and monthly observed from September/95 to August/96, in two sites from 23 to 27 m (a.s.l.). The length of stems, and the number of live and dead leaves, sprouts and inflorescence were recorded. The growth of Paspalum fasciculatum is synchronised with the terrestrial phase of the hydrological cycle, reaching during the period of the study a maximum length of 4.53 m. The dormancy and ability of stems to survive subsequent years under flood, and the tolerance of the species to a highly unstable environment allow us to classify it as a extremely adapted "r" strategist, representing the first stages of colonisation on the sedimentary margins of rivers and lakes in the várzea.
Life cycle and ecology of Paspalum fasciculatum Willd. ex. Fluegge (Poaceae), in the várzea of the central Amazon
Keywords: Paspalum Fasciculatum; Life Cycle; Flood-plains; Várzea; Central Amazon; Paspalum Fasciculatum; Ciclo De Vida; Áreas Inundáveis; Várzea; Amazônia